2009
DOI: 10.17221/951-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity in Variously Prepared Elderberry Foods and Supplements

Abstract: Antioxidant capacity of foods and food supplements based on berries and flowers of medicinal plant elderberry (Sambucus nigra L.) was assessed. Reducing properties of the samples and extracts were evaluated using amperometric detection at working electrode potential -0.8 V after HPLC separation. Moreover, antiradical activity of selected samples was determined by the means of spectrophotometric DPPH radical scavenging method. Electrochemical activity (EA) of fresh juice pressed from elder fruits amounted to 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 7 publications
(6 reference statements)
0
13
0
Order By: Relevance
“…Elderflower extracts are recognized to have anticatarrhal, diuretic, and antiinflammatory properties (Cejpek et al, 2009). Bhattacharya et al (2013) reported that elderflowers also have antidiabetic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Elderflower extracts are recognized to have anticatarrhal, diuretic, and antiinflammatory properties (Cejpek et al, 2009). Bhattacharya et al (2013) reported that elderflowers also have antidiabetic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Infusions of flowers are known to have diaphoretic, anticatarrhal, diuretic and anti-inflammatory functions. 5 Most of the studies on black elder have been performed on the fruits (elderberries), which are known for their antiviral and immunity-boosting effects. 6 Recent research has also revealed potential antidiabetic properties of black elder flowers (elderflowers).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Rutin was identified as the predominant quercetin glycoside in Amaranthus species (Kalinova & Dadakova, ), and it varied between the different Amaranthus spp, in descending order : A. hybrids (27,500 mg/kg DW) > A. hypochondriacus (13,950 mg/kg DW) ≥ A. retroflexus (13,050 mg/kg DW) > A. caudatus (12,010 mg/kg DW) > A. tricolor (2385 mg/kg DW) (Kalinova & Dadakova, ). Rutin content in A. hybrids and A. hypochondriacus is higher than the concentration reported in Elder flower tea (10,900 mg/kg DW) (Cejpek, Malouskova, Konecny, & Velisek, ). Furthermore, A. hybrids and A. cruentus can be recommended as rich sources of rutin and these two Amarathus spp can provide 10–20 kg of rutin/hectare (Kalinova & Dadakova, ).…”
Section: Dietary Phytochemicals In Traditional Leafy Vegetablesmentioning
confidence: 62%